Affinity sorption analysis of the structure of poly(G)·poly(C) complex obtained by means of template-dependent synthesis - Surzhik, M.A.; Timkovsky, A.L. (Биополимеры и клетка, 1993)
The analysis of the structure of poly(G)·poly (C) complexes obtained by the enzymatic synthesis on poly(C) template was carried out using the method of affinity sorption. This latter was used also for the purification of the synthesized so far complexes from the redundant template as well as for the investigation of the structure of poly(G) ·poly(C) complexes obtained by the «traditional» mixing of complementary homopo-lynucleotides. It was shown that the degree of template transcription depends on the quality of RNA polymerase and the incompleted transcription is connected with the inhibition of the elongation of poly(G) chain.